QRIS in the Hands of Gen Z: Balancing Lifestyle, Literacy, and Locus of Control - Iqnatia; Sandhika Cipta Bidhari (JAF (Journal of Accounting and Finance), 2026)
The rapid adoption of digital payment systems, specifically QRIS, has fundamentally transformed the consumption patterns and financial habits of Generation Z. However, this digital shift presents significant challenges, as a consumptive lifestyle, insufficient financial literacy, and diminished self-control often hinder the development of prudent financial management. This study investigates the impact of financial literacy, lifestyle, and locus of control on the financial management behavior of 100 Gen Z QRIS users in Jakarta. Employing a quantitative approach with purposive sampling, the criteria included individuals aged 17–28 who utilize QRIS at least three times monthly. Data were analyzed using multiple linear regression via SPSS 26. The findings demonstrate that financial literacy, lifestyle, and locus of control, both partially and simultaneously exert a positive and significant influence on the financial management behavior of Generation Z in the digital payment ecosystem.